2017
DOI: 10.1017/s1355617717000844
|View full text |Cite
|
Sign up to set email alerts
|

Emotions Are Rising: The Growing Field of Affect Neuropsychology

Abstract: Thirty years ago, the neuropsychology of emotion started to emerge as a mainstream topic. Careful examination of individual patients showed that emotion, like memory, language, and so on, could be differentially affected by brain disorders, especially in the right hemisphere. Since then, there has been accelerating interest in uncovering the neural architecture of emotion, and the major steps in this process of discovery over the past 3 decades are detailed in this review. In the 1990s, magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 178 publications
(189 reference statements)
1
10
0
2
Order By: Relevance
“…Early studies on the subcortical route observed specifically right-sided BOLD responses during non-conscious fearful face viewing (Morris et al, 1999; Morris et al, 1998), and a previous tractography study has also found that only the fractional anisotropy of the right subcortical route was significantly related to threat-biased saccades (Koller et al, 2018). There is mounting evidence for right-sided specialisation for ordered (Wyczesany et al, 2018) and disordered (McDonald, 2017) emotion processing, particularly for non-conscious signals transmitted along the subcortical route (Gainotti, 2012). Thus, our results lend support to this theory by demonstrating evidence for the right pulvinar-amygdala connection’s stronger fibre density and its relationship to emotional face viewing and fearful face recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on the subcortical route observed specifically right-sided BOLD responses during non-conscious fearful face viewing (Morris et al, 1999; Morris et al, 1998), and a previous tractography study has also found that only the fractional anisotropy of the right subcortical route was significantly related to threat-biased saccades (Koller et al, 2018). There is mounting evidence for right-sided specialisation for ordered (Wyczesany et al, 2018) and disordered (McDonald, 2017) emotion processing, particularly for non-conscious signals transmitted along the subcortical route (Gainotti, 2012). Thus, our results lend support to this theory by demonstrating evidence for the right pulvinar-amygdala connection’s stronger fibre density and its relationship to emotional face viewing and fearful face recognition.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to clarify that the exclusion of emotional and social variables, when designing and implementing assistive technologies for PwD, is a problem that reflects a broader limitation of the field of NR itself. Only recently emotional and social dimensions have become central elements of NR theoretical models (McDonald, 2017;Bowen, Yeates & Palmer, 2010;Wilson & Gracey, 2009), slowly permeating the treatment of PwD . As a consequence, the operationalization of these variables, in terms of how to assess and monitor them, both in clinical and research settings, has been significantly slower compared to cognitive functions.…”
Section: Expanding the Scope Of Technology-based Interventionsmentioning
confidence: 99%
“…Social cognition was originally identified through the social psychology literature and is a multifaceted construct referring to the ability to perceive, interpret, and generate responses to the intentions and behaviors of others (see McDonald, 2017, for a comprehensive review; McDonald, Flanagan, & Rollins, 2011; McDonald, Flanagan, Rollins, & Kinch, 2003). Examples of social cognition tasks include identifying emotions, theory of mind (ability to understand and attribute others’ mental states), and knowledge of social pragmatics (Green, Olivier, Crawley, Penn, & Silverstein, 2005).…”
Section: Scientific Advancements In Neuropsychological Assessmentmentioning
confidence: 99%